Effect of Service Quality, Product Quality, and Trust In Customer Satisfaction (Case Study at Bank BRI Syariah KCP Kendal) - Heny Yuningrum; Muyassarah Muyassarah; Risma Dewi Astuti (AL-ARBAH: Journal of Islamic Finance and Banking, 2020)
Purpose - This study aims to determine the effect of service quality, product quality, and trust on customer satisfaction (a case study at Bank BRI Syariah KCP Kendal).Method - The type of research carried out is a quantitative approach. The study population was all customers at Bank BRI Syariah KCP Kendal using the incidental sampling technique. Data were collected through a questionnaire or questionnaire with a Likert scale. This study uses validity and reliability tests, then classic assumption test, t test, F test, determination test and multiple linear regression equation test.Result - The results of this study are (1) service quality has a positive and significant effect on customer satisfaction (2) product quality has a positive and significant effect on customer satisfaction (3) trust has a positive and significant effect on customer satisfaction (4) service quality, product quality, and Trust together has a positive and significant effect on customer satisfaction.Implication - The implication is that service delivery and product quality as well as the trust given by the bank will affect customer satisfaction.Originality - This study shows that these three variables have a significant correlation to customer satisfaction.